Study on the Use of Coal Bottom Ash as a Raw Material Replacement for the Production of Clay Bricks - José Fernando Benítez-Vivas; Juan Pablo Gutiérrez-López; Janneth Torres-Agredo; Luisa Fernanda Mosquera-Idrobo; Miguel Fernando Díaz-Huertas (Ingeniería, 2023)
Context: Masonry bricks are one of the most widely used building materials in the world, which leads to the overexploitation of its raw materials. Its production consumes a large amount of energy and has a large environmental footprint. The clay brick industry can add residues to its raw materials; among those reported are tea processing waste, brick waste, paper industry residues, waste from coffee mills, and coal ashes.